The effect of deviations in sintering temperature on the translucency and color of multi-layered zirconia - Fan Yang; Luyao Zhang; Minghui Yang; Jianfeng Chen; Wenzhong Xing (BMC, 2024)
Abstract Object This study aimed to investigate the changes in the translucency and color of four different multi-layered zirconia materials when the sintering temperature were inaccurate. Materials and methods Two hundred zirconia samples (11 × 11 × 1.0 mm) of four multi-layered zirconia, Upcera TT-GT (UG), Upcera TT-ML (UM), Cercon xt ML (CX), and Lava Esthetic (LE), were divided into five subgroups according to the sintering temperature: L1 (5% lower temperature), L2 (2.5% lower temperature), R (recommended sintering temperature), H2 (2.5% higher temperature), H1 (5% higher temperature). After sintering, color coordinates were measured. Then the translucency parameter (TP) values, and the color differences (between the inaccurate sintering temperature and the recommended temperature) of each zirconia specimen were calculated. Statistical analysis was performed by using three-way ANOVA tests, the one-way ANOVA, and Tukey's post hoc test. Results Three-way ANOVA results showed that material type, sintering temperature, specimen section, and their interactions significantly influenced the TP values (except for the interactions of specimen section and sintering temperature) (P < .05). TP values of zirconia specimens were significantly different in the inaccurate sintering temperatures (P < .05), except for the cervical and body sections of UG group (P > .05). Compared with recommended sintering temperature, higher sintering temperature caused higher TP values for CX, but lower for LE. Three-way ANOVA results showed that material type, sintering temperature, and their interactions significantly influenced the ∆E 00 values (P < .05). There were no significant differences in ∆E 00 values of UM and CX groups at different inaccurate sintering temperatures, and were clinical imperception (except for UM-L1) (∆E 00 < 1.25). ∆E 00 values of all zirconia specimens showed clinically acceptable (∆E 00 < 2.23). Conclusion The deviations in sintering temperature significantly influenced the translucency and color of tested multi-layered zirconia. The trends of translucency in the multi-layered zirconia depended on material type and the color changes of all zirconia materials were clinically acceptable at inaccurate sintering temperatures.